Arrhopalites colchicus sp. nov. (Collembola: Symphypleona: Arrhopalitidae), the third highly troglomorphic species of the genus from the Caucasus - Vargovitsh, Robert S. (Zootaxa, 2025)
The third highly troglomorphic Caucasian species of the genus Arrhopalites Börner, 1906 is described from Verkhneesherskaya Cave (Upper Eshera Cave) in the Gumishkha Massif, Abkhazia. Along with the two previously described Caucasian species, A. macronyx Vargovitsh, 2012 and A. profundus Vargovitsh, 2022, it belongs to the neustonic-hygropetric life form with a set of specific morphological adaptations: remarkably elongated claws, an enlarged sense organ on the third antennal segment, lamellate edges of the mucro, a well-developed mucronal anterior lamella, thin head and dens setae, and elongated thin body setae. These species occupy strictly limited areas within the southern macroslope of the Bzyb Mountain Range in Abkhazia, specifically in the caves of the Khipsta and Gumishkha karst massifs located between the Khipsta and Gumista rivers, at elevations from 530 to 2,000 m a.s.l., representing the world’s highest troglomorphic group within the genus.